RE-IDENTITAS KOTA LAMA MAKASSAR - Asmunandar Asmunandar (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2020)
The origin of the City of Makassar can be traced far in the past, specifically to the time the Kingdom of Gowa-Tallo was conquered by Vereenigde Oost Indische Compagnie (The East India Company or VOC) in 1667. Following the victory, Cornelis Speelman chose one fort later known as Fort Rotterdam to become the center of power and center of government in the east. This Fort Rotterdam is the origin point of the Makassar city planning. The colonial government later replaced VOC in continuing the development of Makassar city by constructing more buildings to support the administration by issuing policies to regulate the inhabitants of the city. This paper offers what can be called “Re-Identity Makassar Old Town” as efforts to give a rooted identity to Makassar city without reviving the colonial policies. Through these conservation efforts, Makassar can become in-site and open space architectural museum. For the inhabitants of Makassar, the conservation of old buildings in the city can portrait the collective activities in the city and its development processes to this day.  Keywords: Re-Identity, Makassar Old Town, Cultural Conservation Author